Preparation of Activated Carbon for the Removal of Pb (II) from Aqueous Solutions - Shrestha, Rajeshwar Man; Pradhananga, Raja Ram; Varga, Margit; Varga, Imre (Journal of Nepal Chemical Society, 2013)
The present study deals with the use of activated carbons prepared from Lapsi seed stone as adsorbents for the removal of Pb (II) ions from aqueous solution. Two series of carbon have been prepared from Lapsi seed stones by treating with conc. H2SO4 and a mixture of H2SO4 and HNO3 in the ratio of 1:1 by weight for removal of metal ions. Chemical characterization of the resultant activated carbon was studied by Fourier Transform Infrared Spectroscopy and Boehm titration which revealed the presence of oxygen containing surface functional groups like carboxylic, lactonic, phenolic in the carbons. The effect of pH and initial metal ion concentration on the adsorption was studied in a batch process mode. The optimum pH for lead adsorption is found to be equal to 5. The adsorption data were better fitted with the Langmuir equations than Freundlich adsorption equation to describe the equilibrium isotherms. The maximum adsorption capacity of Pb (II) on the resultant activated carbons was 277.8 mg g-1 with H2SO4 and 423.7 mg g-1 with a mixture of H2SO4 and HNO3. The waste material used in the preparation of the activated carbons is inexpensive and readily available. Hence the carbons prepared from Lapsi seed stones can act as potential low cost adsorbents for the removal of Pb (II) from water. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8114 Journal of Nepal Chemical Society Vol. 28, 2011 Page: 94-101 Uploaded Date: May 24, 2013